Structural features and interest-rate dynamics of Russia's interbank lending market - Alexey Egorov; Olga Kovalenko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
Russian banks exhibit a range of behaviors that have led to distinct segmentation within the interbank lending market. This paper provides an overview of the core groups of banks operating in the market (state banks, private banks, and foreign-owned banks), as well as a discussion of their assets and liability structures. The 2007-2010 financial crisis had considerable impact on the Russian financial sector. As conditions deteriorated and recovered in global money markets, Russian banks adjusted their behavior with respect to other domestic banks and foreign banks. We conduct a comparative analysis of the Russian inter-bank lending market structure in the pre-crisis period and during recovery to reveal the tactical shifts in the various bank groups.
URN:NBN:fi:bof-201408072198
Keywords: C22; E43; E44; 330; interbank markets; Russia; interest rates